An analysis of PIK3CA hotspot mutations and response to neoadjuvant therapy in patients with breast cancer from four prospective clinical trials - Jank, Paul; Karn, Thomas; van Mackelenbergh, Marion; Lindner, Judith; Treue, Denise; Huober, Jens; Engels, Knut; Solbach, Christine; Diebold, Kurt; Marmé, Frederik; Müller, Volkmar; Schneeweiss, Andreas; et al. (Clinical cancer research, 2024)
The PI3K signaling pathway is frequently dysregulated in breast cancer, and mutations in PIK3CA are relevant for therapy resistance in HER2-positive (HER2pos) breast cancer. Mutations in exons 9 or 20 may have different impacts on response to neoadjuvant chemotherapy-based treatment regimens.We investigated PIK3CA mutations in 1,691 patients with early breast cancer who were randomized into four neoadjuvant multicenter trials: GeparQuattro (NCT00288002), GeparQuinto (NCT00567554), GeparSixto (NCT01426880), and GeparSepto (NCT01583426). The role of different PIK3CA exons and hotspots for pathologic complete response (pCR) following neoadjuvant chemotherapy (NACT) and patient survival were evaluated for distinct molecular subgroups and anti-HER2 treatment procedures.A total of 302 patients (17.9%) of the full cohort of 1,691 patients had a tumor with a PIK3CA mutation, with a different prevalence in molecular subgroups: luminal/HER2-negative (HER2neg) 95 of 404 (23.5%), HER2pos 170 of 819 (20.8%), and triple-negative breast cancer 37 of 468 patients (7.9%). We identified the mutations in PIK3CA exon 20 to be linked with worse response to anti-HER2 treatment (OR = 0.507; 95% confidence interval, 0.320-0.802; P = 0.004), especially in hormone receptor-positive HER2-positive breast cancer (OR = 0.445; 95% confidence interval, 0.237-0.837; P = 0.012). In contrast, exon 9 hotspot mutations p.E452K and p.E545K revealed no noteworthy differences in response therapy. Luminal/HER2neg patients show a trend to have worse treatment response when PIK3CA was mutated. Interestingly, patients with residual disease following neoadjuvant treatment had better survival rates when PIK3CA was mutated.The PIK3CA hotspot mutation p.H1047R is associated with worse pCR rates following NACT in HER2pos breast cancer, whereas hotspot mutations in exon 9 seem to have less impact.
Online veröffentlicht: 3. September 2024
Gesehen am 12.11.2024